SETT-Net: A network for software engineering training and teaching - Zdravkova, Katerina; Bothe, Klaus; Budimac, Zoran (IEEE, 2003)
The intention of the SETT-Net is to enable the usage of shared training and teaching resources for a software engineering course in eight schools and in four countries. The network is completely Web-based. It consists of a Centre Point at Humboldt University in Berlin and four National Centres, in Berlin, Novi Sad, Plovdiv and in Skopje. This paper presents the syllabus, the teaching materials of the joint SE course, the network architecture and its contents.
Keywords: Computing Curricula, eLearning